Kebijakan Pemerintah Daerah Kota Bukittinggi dalam Mengoptimalkan Penerimaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (Pbb-P2) (Studi Kasus: Kelurahan Kubu Tanjung) - Fadila Fadila; Miswardi Miswardi (Lembaga Yasin AlSys, 2026)
The collection of rural and urban land and building tax (PBB-P2) in Kubu Tanjung Urban Village remains suboptimal, with realized revenue reaching only 29% of its potential, creating a gap between tax capacity and actual receipts and constraining the availability of funds for local development. This study aimed to analyze the policies of the Bukittinggi City Government in optimizing PBB-P2 revenue and to identify the factors that contribute to the low tax awareness of residents in Kubu Tanjung Urban Village in fulfilling their tax obligations. A qualitative approach was employed, with data collected through observation, interviews, and documentation involving village officials and registered taxpayers in Kubu Tanjung Urban Village. The findings show that the policy measures for optimizing PBB-P2 revenue have not been implemented effectively. The low realization of tax revenue is primarily influenced by (1) limited taxpayer awareness and compliance, (2) unstable community economic conditions, with most residents depending on the agricultural sector with uncertain incomes, (3) suboptimal socialization and dissemination of tax information, and (4) collection efforts that are largely confined to the distribution of Tax Due Notification Letters (SPPT) without firm law enforcement at the village level. Although the services provided by village officials are considered adequate and active, economic constraints and low public awareness remain the main obstacles. This study concludes that strengthening PBB-P2 optimization policies must be accompanied by increased intensity and quality of socialization as well as support for community economic empowerment, so that tax payment compliance can improve and local development objectives can be achieved more optimally.